2004
DOI: 10.1002/art.20633
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic heterogeneity among Spanish patients with recurrent autoinflammatory syndromes associated with the CIAS1/PYPAF1/NALP3 gene

Abstract: Objective. To investigate the involvement of the CIAS1/PYPAF1/NALP3 gene in 7 unrelated Spanish families with recurrent autoinflammatory diseases characterized by early onset, recurrent fever, and a chronic urticarial rash, in whom a clinical diagnosis of cryopyrin-associated periodic syndromes (CAPS) is suspected.Methods. Clinical symptoms, results of laboratory analyses, and data on previous treatments in members of the 7 families were recorded on a questionnaire specific for hereditary autoinflammatory dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 15 publications
(33 reference statements)
7
65
0
1
Order By: Relevance
“…In this regard, the identification of a nonsense mutation in PYPAF1 (c.1660CϾT, exon 3) calls into question the current nosology of hereditary recurrent fever syndromes and suggests that defects in PYPAF1 may also underlie "FMF-like" disorders. Of note, the mutation was also found in the patient's mother, who did not exhibit any clinical manifestations; this finding is consistent with the notion of incomplete penetrance of the disease phenotype, an observation already reported in several families with PYPAF1 mutations (8,25,27).…”
Section: Discussionsupporting
confidence: 89%
“…In this regard, the identification of a nonsense mutation in PYPAF1 (c.1660CϾT, exon 3) calls into question the current nosology of hereditary recurrent fever syndromes and suggests that defects in PYPAF1 may also underlie "FMF-like" disorders. Of note, the mutation was also found in the patient's mother, who did not exhibit any clinical manifestations; this finding is consistent with the notion of incomplete penetrance of the disease phenotype, an observation already reported in several families with PYPAF1 mutations (8,25,27).…”
Section: Discussionsupporting
confidence: 89%
“…In a family presenting with an atypical autoinflammatory syndrome we identified the R488K mutation, which was previously reported in a Spanish family with FCAS-like symptoms (42). Further investigation of the family in the present study revealed 2 asymptomatic family members who were carriers for R488K, supporting the notion that this is a reduced-penetrance CIAS1 mutation as proposed earlier (42). We screened 740 Caucasian control chromosomes and found R488K in 1 of 740; we thus estimated an R488K allele frequency of 0.0014 in the healthy Caucasian population.…”
Section: Resultssupporting
confidence: 56%
“…60 Roughly 85% of CIAS1 mutations occur in exon 3. 62,63 Cryopyrin is one of the constituents of the inflammasome, which plays a key role in the regulation of intracellular defense in response to bacterial toxins and compounds released during cell injury or stress. 22,64,65 This protein is essential for activation of caspase-1, the enzyme that cleaves pro-IL1-β into its active form, IL1-beta, which in turn is a major proinflammatory cytokine.…”
Section: Tnf Receptor Associated Periodic Syndrome (Traps)mentioning
confidence: 99%